(untitled) (Advancements in Homeopathic Research, 2023)
Diabetes mellitus is considered as the most important public health threat which has affected millions of people around the globe of all gender, ages, ethnic groups and race. Homoeopathy being a system of holistic approach, there are remedies based on the individualizing characteristic symptoms. In homoeopathic system Galega officinalis mother tincture is one among the antihyperglycemic medicine. Aqueous and ethanolic extract of Galega officinalis showed a hypoglycaemic effect in our research study. Thirty clinically diagnosed cases of T2DM were taken for the study. Most of the patients have got relief both symptomatically and diagnostically Hence, this study shows that Galega officinalis mother tincture is effective in treating type II Diabetes mellitus [1].